User Centered Design (UCD) Method to Design Regional Dance Application Based on Multimedia - Jimmi Hendrik P. Sitorus; Allwine Allwine (Jurnal Mantik, 2020)
Regional dances are generally less attractive to Indonesian people today. Because regional dance is seen as something that is not interesting, especially for teenagers today. Regional dance seems increasingly marginalized or neglected and very few people who know regional dance from each region itself. Regional Dance Application is a multimedia-based application that can display information on regional dance to the public in the form of images, videos and audio through information media, namely computers. With this application, it is considered to be able to speed up or be efficient in typing short messages, so that the time used in typing messages is not too long. UCD (User Centered Design) is a new paradigm in the development of web-based systems. UCD (User Centered Design) is a term used to describe a design philosophy. The concept of UCD (User Centered Design) is the user as the center of the system development process and the purpose or nature of the context and system environment are all based on user experience.